2006
DOI: 10.1016/j.amjmed.2005.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole Treatment for Subacute Invasive and Chronic Pulmonary Aspergillosis

Abstract: In patients with subacute IA and CPA, voriconazole was efficacious as salvage or primary therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 27 publications
(45 reference statements)
6
81
1
7
Order By: Relevance
“…39 A similar trial performed later involved 36 patients with subacute invasive and chronic pulmonary aspergillosis who were receiving voriconazole as primary or salvage therapy. 40 The rates of therapeutic response and toxic effects were comparable to those observed by Denning and others. 24 Smaller observational studies and case reports have also demonstrated the efficacy of voriconazole for treatment of invasive aspergillosis in specific populations of immunocompromised patients.…”
Section: Aspergillosissupporting
confidence: 72%
See 1 more Smart Citation
“…39 A similar trial performed later involved 36 patients with subacute invasive and chronic pulmonary aspergillosis who were receiving voriconazole as primary or salvage therapy. 40 The rates of therapeutic response and toxic effects were comparable to those observed by Denning and others. 24 Smaller observational studies and case reports have also demonstrated the efficacy of voriconazole for treatment of invasive aspergillosis in specific populations of immunocompromised patients.…”
Section: Aspergillosissupporting
confidence: 72%
“…For invasive pulmonary aspergillosis, the recommended treatment duration is a minimum of 6 to 12 weeks, whereas chronic pulmonary aspergillosis may require treatment with voriconazole for several months. 16,40 Rarely would a patient be receiving voriconazole for less than 2 weeks, especially given that empiric therapy with voriconazole in febrile neutropenia is not recommended. In summary, if TDM is indicated (as determined by earlier steps in the algorithm shown in Figure 1), the duration of voriconazole therapy is adequate and appropriate to allow TDM to be performed and patient therapy to benefit.…”
Section: Duration Of Therapymentioning
confidence: 99%
“…The common characteristics of these forms, however, consist of 1) underlying pulmonary disorders, 2) the status of low-grade immunosuppression, and 3) less than severe findings of angioinvasion in histopathology. 1,5,7 Numerous clinical cases and few retrospective studies have been reported for the treatment of CPA [8][9][10][11][12] ; however, there are no large-scale clinical trials have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…(1,2). However, in previous reports, the majority of patients with CNPA have been diagnosed according to clinical criteria (3)(4)(5)(6). We conducted a histopathological study of lung specimens obtained by autopsy, surgical resection, or biopsy to clarify the characteristic pathological and clinical features of CNPA, which was diagnosed in a total of 4 patients.…”
mentioning
confidence: 99%